Faktor Risiko Kontaminasi Salmonella Spp. Pada Daging Ayam Broiler (Gallus Gallus Domestica) Yang Dijual di Pasar Banguntapan - Ubaidillah Ubaidillah; Handa Haryati (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2023)
Background of Study: Chicken is a food ingredient with high nutritional value that is consumed by  community, the high nutritional value of chicken meat makes it a food ingredient that is susceptible to biological hazards. One of the microbes that contaminate chicken meat is Salmonella Spp. These bacteria cause disease by food borne transmission and are mostly pathogenic. This pollution is caused by the environment, handling and marketing errors. The purpose of this study is to determine the risk factors for contamination of Salmonella Spp. on Broiler Chicken sold at Banguntapan MarketMethods: This research method was quantitative research with a cross sectional approach. The population of all chicken traders in the Banguntapan market. The sampling technique used purposive sampling technique, and the data were analyzed using the Chi Square Test.Results: The results of data analysis, there was a significant influence between environmental factors on Salmonella Spp contamination on Broiler Chicken with a p value of (0.033 0.05). There was a significant influence between Hygiene factors and seller activity on Salmonella Spp contamination on broiler meat with a p value of (0.013 0.05). There was a significant effect between the pH factor on Salmonella Spp contamination on broiler chicken with a p value of (0.0100.05). There is no significant effect of temperature on Salmonella Spp contamination on Broiler Chicken with a p value of (0.3510.05)Conclusions: Risk Factor in this research, there was a significant influence between the selling environment, hygiene and seller activities, and pH on the risk of Salmonella Spp contamination in Broiler Chicken (Gallus gallus domestica), and there was no significant effect between temperature and contamination of Salmonella Spp. on Broiler Chicken (Gallus gallus domestica) at Banguntapan MarketKeywords: Salmonella Spp; broiler chicken; Gallus gallus domesticus